124k views
4 votes
What are the steps to do -2(y+6)=y+3+2y

User Vladfau
by
5.3k points

1 Answer

5 votes
First of all, let's simplify the equations by adding and multiplying everything.
-2(y+6)=y+3+2y
Add 2y and y on the right side:
-2(y+6) = 3y+3
Distribute -2y into the parentheses:
-2y - 12 = 3y + 3
Subtract both sides by -2y - 12, so you have one side that equals zero:
5y + 15 = 0
Subtract both sides by 15:
5y = -15
Divide both sides by 5:
y = -3
User Moiz
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.